2022
DOI: 10.7759/cureus.30071
|View full text |Cite
|
Sign up to set email alerts
|

Applicant Selection for Anesthesiology Residency Programs in Saudi Arabia

Abstract: BackgroundAnesthesiology is a medical specialty that involves pre, intra, and postoperative surgical and medical procedures; it is a profession shaped by the clinician's medical knowledge and manual dexterity. To date, very few studies have addressed the selection criteria and factors associated with the applicant selection process for anesthesia residency programs in Saudi Arabia. ObjectivesWe aimed to define the criteria, factors, and guidelines for candidate selection in anesthesia residency programs in Sau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It has been reported that Saudi residency program directors in competitive specialties, such as plastic surgery, anesthesiology, and urology, prefer candidates who have high-quality research publications. [27][28][29] In contrast, specialties that are relatively less competitive in Saudi Arabia, such as internal medicine, obstetrics and gynecology, family medicine, and pediatrics have fewer publications. 30 This issue extends to the United States as orthopedic residency program applicants list research projects in their resumes as 'submitted'; but, in reality, remain frequently unpublished or published in low-impact journals.…”
Section: Influntial Factors Towards Conducting Medical Researchmentioning
confidence: 99%
“…It has been reported that Saudi residency program directors in competitive specialties, such as plastic surgery, anesthesiology, and urology, prefer candidates who have high-quality research publications. [27][28][29] In contrast, specialties that are relatively less competitive in Saudi Arabia, such as internal medicine, obstetrics and gynecology, family medicine, and pediatrics have fewer publications. 30 This issue extends to the United States as orthopedic residency program applicants list research projects in their resumes as 'submitted'; but, in reality, remain frequently unpublished or published in low-impact journals.…”
Section: Influntial Factors Towards Conducting Medical Researchmentioning
confidence: 99%